Proceedings of the International Conference on Economics, Management and Technologies 2020 (ICEMT 2020) 2020
DOI: 10.2991/aebmr.k.200509.042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Exchange Rates and Oil Price: Adaptive Analysis and Forecasting

Abstract: Multivariate generalizations of the modified and adaptive time series correlation coefficients are obtained using the example of the dependence of currency pairs quotations and Brent crude oil price. The analysis of the movement of exchange rates and oil price in the R software environment. A much more detailed data analysis than the classical theory suggestion is obtained. Based on the identified trends in the dynamics of these markets, short-term forecasting was carried out using ARIMA, TBATS models and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…In [5], using the example of currency quotes, it is shown that, despite similar values, the adaptive coefficient is more sensitive than the modified correlation coefficient. Let's analyse the financial time series using an adaptive correlation coefficient.…”
Section: Analysis Of Financial Time Series Using the Adaptive Correlation Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5], using the example of currency quotes, it is shown that, despite similar values, the adaptive coefficient is more sensitive than the modified correlation coefficient. Let's analyse the financial time series using an adaptive correlation coefficient.…”
Section: Analysis Of Financial Time Series Using the Adaptive Correlation Coefficientmentioning
confidence: 99%
“…According to the graphs obtained, a fall in the rates of Bitcoin and gold is predicted. The work [5] shows the analysis of the movement of oil prices and their fall in the long term. The behaviour of all the variables under consideration is similar; accordingly, when analysed, the adaptive correlation coefficient will show a strong positive relationship.…”
Section: Analysis Of Financial Time Series In the R Software Environmentmentioning
confidence: 99%